2020
DOI: 10.21037/jtd-2020-icc-005
|View full text |Cite
|
Sign up to set email alerts
|

Methods for assessing cough sensitivity

Abstract: of assessing the cough severity mainly include the cough scores, visual analogue scale (3) and QoL questionnaires like the Leicester cough questionnaire (LCQ) (4), coughspecific quality of life questionnaire (CQLQ) (5) etc. They are easy to score and also practical for a longitudinal comparison in clinical practice. However, they are susceptible to individual factors and are unlikely to be used for a horizontal comparison. Besides, cough can be assessed objectively with cough frequency monitoring and cough cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 117 publications
0
24
0
Order By: Relevance
“…18,19 Cough inhalation challenges have been previously performed using acidic agents (e.g., citric acid, acetic acid and tartaric acid) and other stimulants such as capsaicin. 20,21 However, widespread clinical use of these agents has been limited by the need for specialized equipment, general tolerability and uncertainty surrounding significance of results. 22 Mannitol is readily available in most lung function laboratories and reasonably well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Cough inhalation challenges have been previously performed using acidic agents (e.g., citric acid, acetic acid and tartaric acid) and other stimulants such as capsaicin. 20,21 However, widespread clinical use of these agents has been limited by the need for specialized equipment, general tolerability and uncertainty surrounding significance of results. 22 Mannitol is readily available in most lung function laboratories and reasonably well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical animal studies, the invasive intratracheal mechanical stimulation was found to induce the cough reflex in anaesthetised rabbits/cats/dogs (16)(17)(18)(19)(20). For humans in clinical practice, the common area where the mechanical stimulation has been applied are the large airways level and the chest (8,9). In 2004, Lee and Eccles reported the first study to elicit cough in humans by the vibration of the airway at the trachea level with a modified men's shaver.…”
Section: Mechanical Challenge Testsmentioning
confidence: 99%
“…Twenty-four-hour cough counting is a semi-objective assessment and has been suggested as the best method to quantify cough ( 6 ), but due to its labour-intensive and time-consuming nature, it has been largely confined to the research setting. Finally assessing cough reflex sensitivity, usually by inhalational challenge, can be used to dissect the pathophysiologic mechanisms of cough and evaluate the effect of drug intervention in clinical trials ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several PROMs can be used for assessment of LSD (see methods). These questionnaires provide easily obtainable subjective baseline data which can then be used to monitor patient progress and treatment outcomes [ 26 ].…”
Section: Introductionmentioning
confidence: 99%